“Strong Defender of Russian Foundations”: I. S. Aksakov in the Evaluation of Petersburg Slavophiles - Alexey Valerievich Malinov; Izolda Yurievna Peshperova (Управленческое консультирование)
The article discusses the history of relations slavophiles Petersburg, St. Petersburg University professor Orest Fedorovich Miller (1833-1889) and Konstantin Nikolayevich Bestuzhev-Ryumin (1829- 1897) and Ivan Sergeyevich Aksakov (1823-1886). The article is used both published and not published materials, mainly correspondence of scientists. Estimates of the person and work of I. S. Aksakov from the St. Petersburg professors. Indicates that the St. Petersburg Slavophiles not only highly valued publicistics of I. S. Aksakov, but his active public and publishing activities.